Comparative Analysis of Chlorella vulgaris Cell Densities in Different Culture Systems - Shalehah, Atiatun; Diamahesa, Wastu Ayu (Program Studi Budidaya Perairan Universitas Mataram, 2025)
Chlorella vulgaris is a cosmopolitan microalga with high nutritional value, widely utilized in aquaculture, pharmaceuticals, and biofuel production. This study evaluated its growth performance across three culture scales (laboratory bottle, carboy, and intermediate concrete tank) at BPBAP Situbondo from February to June 2024. The research aimed to analyze the influence of scale on biomass productivity and identify critical environmental factors. Results demonstrated significant growth variations among scales. The laboratory bottle (5 L) achieved the highest cell density (54 × 10⁶ cells/mL) on day 11, attributed to optimal light distribution and stable temperature (30–33°C). Carboy cultures (10 L) showed moderate productivity (31 × 10⁶ cells/mL), while the intermediate scale (700–800 L) yielded the lowest density (6.8 × 10⁶ cells/mL) due to light limitation and suboptimal aeration. Water quality parameters remained stable across all systems, with pH 8.0, salinity 30–34 ppt, and uniform light intensity (500 lux). Statistical analysis confirmed significant differences in growth rates (p < 0.05), highlighting the inverse relationship between scale size and productivity. The study concludes that small-scale systems offer superior environmental control for C. vulgaris cultivation. For mass production, design improvements—such as enhanced aeration, closed photobioreactors, and artificial lighting—are recommended to replicate laboratory-scale efficiency. These findings provide actionable insights for optimizing microalgae culture systems in aquaculture feed production.